2015
DOI: 10.1098/rspb.2015.2207
|View full text |Cite
|
Sign up to set email alerts
|

Phage selection for bacterial cheats leads to population decline

Abstract: While predators and parasites are known for their effects on bacterial population biology, their impact on the dynamics of bacterial social evolution remains largely unclear. Siderophores are iron-chelating molecules that are key to the survival of certain bacterial species in iron-limited environments, but their production can be subject to cheating by non-producing genotypes. In a selection experiment conducted over approximately 20 bacterial generations and involving 140 populations of the pathogenic bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 63 publications
(107 reference statements)
0
25
0
Order By: Relevance
“…Conversely, resource competition was likely more intense and more symmetric within lasR communities due to stronger levels of phage resistance evolution (and hence higher P. aeruginosa density). Lastly, it has been shown that phage selection can impose relatively higher competitive cost for the PAO1 compared to the lasR strain due to upregulation of siderophore production (Vasse, Torres-Barcelo, & Hochberg, 2015). Such metabolic cost could also potentially explain relatively poorer PAO1 growth in the presence of competitors even in the nonsocial culture conditions used in this experiment.…”
Section: Discussionmentioning
confidence: 86%
“…Conversely, resource competition was likely more intense and more symmetric within lasR communities due to stronger levels of phage resistance evolution (and hence higher P. aeruginosa density). Lastly, it has been shown that phage selection can impose relatively higher competitive cost for the PAO1 compared to the lasR strain due to upregulation of siderophore production (Vasse, Torres-Barcelo, & Hochberg, 2015). Such metabolic cost could also potentially explain relatively poorer PAO1 growth in the presence of competitors even in the nonsocial culture conditions used in this experiment.…”
Section: Discussionmentioning
confidence: 86%
“…Phage-or phage-like structures spontaneously inducing cell lysis are frequently reported to be involved in the bacterial biofilm formation process (Godeke et al, 2011;Turnbull et al, 2016). Although the underlying molecular mechanism of SPI remains unknown, the lysis of individual cells may benefit the population through the release of 'public goods' such as eDNA (Vasse et al, 2015;Attar, 2016;Saucedo-Mora et al, 2017). Moreover, P2Sp-encoded genes also increase biofilm formation, and many of them are expressed at intermediate levels in wild-type W3-18-1.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal frequency for nonproducers appears to be low. When initially very frequent (75%), nonproducers did not evolve substantially higher frequencies of resistance compared with their populations in monoculture, possibly as uncommon producers yielded a low pyoverdin concentration, thereby contributing relatively little both to nonproducer growth (20) and to the generation of resistant variants. An additional experiment (SI Appendix) confirmed that differences in growth and antibiotic resistance between producers and nonproducers are mediated by pyoverdin availability and production: when populations grew under high iron availability conditions (i.e., where siderophores are not needed), the nonproducers did not invade the mixed populations (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that this effect occurs because the investment in cooperative secretions limits growth and thereby competitive ability. Alternatively, in some particular cases, antagonisms may directly increase the benefit to nonproducers by inducing the production of costly public goods (20,61). In Staphylococcus aureus, for example, sublethal doses of ciprofloxacin, mupirocin, or rifampicin induce the expression of the costly effector molecule regulating the quorum-sensing system agr, thereby favoring agr-negative variants (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation